2016
DOI: 10.1007/s00066-016-0970-3
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy plus adjuvant chemotherapy versus concurrent chemoradiotherapy in locoregionally advanced nasopharyngeal carcinoma

Abstract: Purpose: This study aimed to compare the efficacy of induction-concurrent (IC-CCRT) with concurrent-adjuvant (CCRT-AC) chemotherapy in patients with locoregionally advanced nasopharyngeal carcinoma (LA-NPC) treated by intensity-modulated radiotherapy (IMRT). Materials and Methods: Data on 834 patients with newly diagnosed, non-metastatic stage III-IVA (except T3N0) NPC receiving either IC-CCRT or CCRT-AC between July, 2004 and December, 2014 were retrospectively reviewed. Propensity score matching (PSM) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The characteristics of the patients included in the 14 eligible studies 17‐30 are shown in Table 1. A total of 4086 participants were involved in this meta‐analysis, of whom 2014 received CCRT with additional chemotherapy and 2072 received CCRT alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the patients included in the 14 eligible studies 17‐30 are shown in Table 1. A total of 4086 participants were involved in this meta‐analysis, of whom 2014 received CCRT with additional chemotherapy and 2072 received CCRT alone.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies 17‐20,23‐25,27,28,30 investigated IC + CCRT, which included 1431 participants. Moreover, four trials 21,22,26,29 explored CCRT + AC in 583 patients. Eleven studies 18‐20,22‐29 involved 1:1 PSM analysis, Two studies 21,30 involved 1:2 PSM analysis, and 2:1 PSM analysis was conducted in only one study 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar results regarding the negative role of adjuvant chemotherapy were observed by Skillington et al, who reported that the addition of adjuvant chemotherapy to a radiotherapy regimen was associated with worse overall survival in patients with p16-positive oropharyngeal squamous cell carcinoma (adjusted HR, 1.46; 95% CI, 0.91-2.33). 23 During adjuvant chemotherapy, a cohort of patients with NPC experienced grade 3-4 dysphagia, nausea, and vomiting, 24,25 leading to weight loss and nutritional deficiency. Indeed, poor nutritional status has a negative influence on overall survival and distant metastasis-free survival in NPC patients, [26][27][28] which may correlate with the negative impacts of adjuvant chemotherapy observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A more intensive systemic therapy such as ACT might be needed. But a certain conclusion of the impact of ACT on locoregionally advanced NPC is still unable to make, through the results of the studies so far (36-38). And ACT plus CCRT was proved to cause more acute adverse reactions such as severe bone marrow suppression and gastrointestinal reactions, compared with CCRT alone (38).…”
Section: Discussionmentioning
confidence: 99%